Speech-therapy intervention guidelines for bilingual children - Nieva, Silvia (Revista de Investigación en Logopedia, 2015)
Growing migration patterns, along with social demands for the use of languages in order to develop both personally and professionally have led to an increasing interest in bilingual education. The Spanish State is one source of emerging institutional support for the implementation of bilingual programs in foreign languages and support for the teaching of co-official languages and regional dialects. Recent investigations claim that bilingualism benefits language development and cognition. However, many questions are still to be resolved in populations that present language disorders. Professionals are faced with a great variety of contexts and bilingual situations, while information on typical and atypical development, and the efficacy of different treatment models is scarce. This review aims to organise the available development-based and evidence-based information so as to provide guidelines to professionals when it comes to taking decisions and counselling families with children who have speaking and language difficulties in bilingual settings.
Keywords: Speech Therapy; Bilingualism; Multilingualism; Evidence-based Practice; Speech-sound disorders; Speech-therapy intervention.